Effects of Low- and High-Dose Valproic Acid and Lamotrigine on the Heart in Female Rats - Yildiz, Azibe; Vardi, Nigar; Parlakpinar, Hakan; Ates, Burhan; Colakoglu, Neriman (Humana Press Inc, 2022)
Epilepsy is a chronic neurological disease that affects more than 50 million people worldwide. Antiepileptic drugs (AEDs) are the mainstay of treatment for most patients with epilepsy. However, AEDs have been reported to be associated with adverse cardiac effects. In this study, it was aimed to investigate the possible cardiac effects of low-dose (LD) and high-dose (HD) treatment of valproic acid (VPA) and lamotrigine (LTG), which are commonly used AEDs, in rats without epilepsy. Rats were randomly grouped as control, LD-VPA, HD-VPA, LD-LTG, and HD-LTG. The cardiac effects of AEDs were evaluated using immunohistological, biochemical, and hemodynamic parameters. A dose-dependent increase in the intensity of caspase-3 staining was detected in the VPA and LTG groups. The intensity of connexin-43 and troponin-T staining in the VPA groups and desmin staining in the LTG groups was significantly reduced. Biochemically, HD-VPA and HD-LTG administrations caused a significant increase in MDA level in myocardial tissue. In addition, as a result of hemodynamic evaluations, cardiac functions were found to be affected and blood pressure increased in HD-LTG group. The results of present study support that VPA and LTG treatment can increase cardiac risk markers.
Keywords: Antiepileptic drug; Cardiotoxicity; Lamotrigine; Myocardium; Valproic acid